Emission taxes, lobbying, and incomplete enforcement - Joschka Gerigk (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In this paper, I analyze incomplete enforcement in a political economy model. I use a contest framework to explain changes in lobbying behavior when special interest groups anticipate the incomplete enforceability of environmental regulation. In this setting, I compare two instruments, namely an abatement standard and an emission tax. Regulation of a polluting output is proposed and two lobby groups - representing the interests of producers and environmentalists, respectively - seek to influence the government in order to prevent or support the implementation of the regulation. I develop a general framework to demonstrate that the lobbying efforts are determined not only by the stringency of the proposed policy - as determined by the level of the tax or abatement standard - but, importantly, also by its enforceability. Using common functional specifications, I then show that, when an emission tax is proposed, incomplete enforcement may not only reduce the industry's opposition to regulation compared to a situation with full enforcement, but it may, despite the possibility of untruthful reporting, also reduce expected environmental damage. When instead an abatement standard is proposed, however, the effects of regulatory stringency and enforceability are ambiguous, rendering unequivocal policy recommendations for this case impossible.
Keywords: D72; L51; Q58; 330